Clinical outcomes of endoscopic submucosal dissection for early stage esophagogastric junction cancer: A systematic review and meta-analysis. Issue 1 (January 2015) - Park, Chan Hyuk; Kim, Eun Hye; Kim, Ha Yan; Roh, Yun Ho; Lee, Yong Chan
Abstract Background Although endoscopic submucosal dissection has become widely used for the management of selected cases of early gastric cancer, the effects of endoscopic submucosal dissection for esophagogastric junction cancer have not been fully evaluated. Methods Medline, Embase, and the Cochrane Library were searched using the primary keywords "endoscopic submucosal dissection, " "ESD, " "endoscopic resection, " "esophagogastric junction, " "gastroesophageal junction, " and "Barrett." Six short-term clinical outcomes and three long-term oncologic outcomes were extracted. Results A total of six studies provided data on 359 early stage esophagogastric junction cancers treated with endoscopic submucosal dissection. The pooled estimate of en bloc resection and complete resection was 98.6% (95% confidence interval 95.9–99.6%) and 87.0% (95% confidence interval 79.7–92.0%), respectively. The pooled estimate of stenosis was 6.9% (95% confidence interval 3.2–14.0%). In 269 lesions with curative resection, there was no local recurrence or distant metastasis. In contrast, three local recurrences and two distant metastases occurred in 90 lesions with non-curative resection. Conclusions Endoscopic submucosal dissection for early stage esophagogastric junction cancer is a feasible treatment option with high en bloc resection, complete resection rates and an acceptable range of complications. When curative resections are achieved, good oncologic outcomes are likely in the management of early stage esophagogastric junction cancer by endoscopic submucosal dissection.